Gravity load effects on the behaviour of reinforced concrete beam critical zones subjected to cyclic loads. (15th February 2019) - Gião, Rita; Lúcio, Valter; Chastre, Carlos
Highlights: Parametric analysis of the gravity load influence on beam critical zones. For higher gravity loads, frame mechanism is associated to 4 beam plastic hinges. The structural hysteretic response is dependent on the load path. A cyclic displacement test shall start with gravity load effects imposition. Abstract: The aim of the present study was to proceed to a numerical analysis of the gravity load effects on the behaviour of reinforced concrete beam critical zones when subjected to cyclic loads. A parametric study to assess the influence of different levels of gravity load on RC beam critical zones subjected to cyclic loading was carried out. For this purpose, assuming the level of gravity load as a variable parameter, a nonlinear numerical model of a beam-column connection, previously calibrated with experimental data, was used. In order to evaluate the gravity load effects in the global response, a numerical study of a RC frame system is also presented. The numerical results are analysed in terms of global hysteretic response, accumulated energy dissipation and equivalent viscous damping ratio. In this numerical study, it was observed that the hysteretic response depends on the load path. In the presence of higher gravity load levels, the structure hysteretic behaviour exhibits higher damage levels, associated to a failure mechanism corresponding to the formation of four span plastic hinges. Thus, the proper test procedure should involve the imposition of a reverse cyclic displacement history starting each cycle from the gravity load effects.